Techno-Economic Feasibility Study of Renewable Energy Power Generation: A Case Study in Sumba Jaya Area, East Nusa Tenggara Province, Indonesia - Aprilianto, Rizky Ajie; Syah, Mario Norman; Anita, Nur (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2025)
The Sumba Island electricity is divided into two central systems, the Waingapu and Waikabubak. The load growth of the Waikabubak system, which is in the Sumba Jaya area, is predicted to be higher than that of the Waingapu system. The existing power generation systems in this area consist of solar PV system (PLTS) Bilacenge along with vanadium redox battery (VRB), micro hydro power plant (PLTMH) Lokomboro and Umbuwango, the diesel power generation (PLTD) Waikabubak and Waitabula (Baru Laratama). The existing configuration of these systems produces renewable energy penetration below 45%. Hence, this condition shows that renewable energy exploration has yet to be carried out optimally, even though this area has an average potential for solar irradiation and wind speed reaching 5.84 kWh/day and 5.29 m/s, respectively. This research proposes an optimization design for developing the electricity system in the Sumba Jaya area, including Sumba Barat and Sumba Barat Daya Regency, East Nusa Tenggara Province. The proposed design searches for the optimal capacity of the existing system by adding renewable energy power generation in the form of wind turbine generation (PLTB) in Wanokaka with a capacity of 3,000 kW. The modelling was conducted using Hybrid Optimization of Multiple Energy Resources (HOMER) software to assess the feasibility of the proposed system. As a result, the payback period of the proposed system is achieved around four years, with the net present cost (NPC) and cost of energy (COE) lower than the existing system. In addition, the level of CO2 emissions was reduced, with the increased renewable energy penetration rate at around 96.6%.